1986
DOI: 10.1192/bjp.148.5.509
|View full text |Cite
|
Sign up to set email alerts
|

Deficits of Chronic Schizophrenia in Relation to Long-Term Hospitalisation

Abstract: Eighty chronic schizophrenic and 16 manic-depressive psychotic patients conforming to Research Diagnostic Criteria were examined in terms of their mental state, cognitive functioning, current behaviour, and neurological status. They comprised out-patients, day-care patients, and long-stay in-patients belonging to two mental hospitals with different social conditions. Assessed deficits were not significantly related to record variables such as age, duration of illness, duration of hospitalisation, or treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
(4 reference statements)
0
5
1
Order By: Relevance
“…It has been suggested that negative symptoms (Crow, 1980) and thought disorder (Carpenter et al, 1988) are enduring and do not respond to neuroleptics or to change in environment (Crow, 1980;Mathai and Gopinath, 1985); at first sight, this appears to have been supported by the findings in this study. It must be remembered, however, that the environment in which these patients were living was relatively stable, at least as compared to that in the 'active' rehabilitation wards or the community.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…It has been suggested that negative symptoms (Crow, 1980) and thought disorder (Carpenter et al, 1988) are enduring and do not respond to neuroleptics or to change in environment (Crow, 1980;Mathai and Gopinath, 1985); at first sight, this appears to have been supported by the findings in this study. It must be remembered, however, that the environment in which these patients were living was relatively stable, at least as compared to that in the 'active' rehabilitation wards or the community.…”
Section: Discussioncontrasting
confidence: 46%
“…In previous studies (Owens and Johnstone, 1980;Johnstone et al, 1985;Mathai and Gopinath, 1985;Wagman et al, 1987;Carpenter et al, 1988;Harris et al, 1992), the incidence of deficit symptoms has varied considerably depending on the nature of the sample and the methods of assessment. Our samples of elderly and younger schizophrenic patients showed a high frequency and severity of negative and disorganization symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not have specific data, there is little reason to believe that our subject groups differ significantly on these factors. Further support for the use of the MMSE in this research comes from its use in similar settings elsewhere (Harvey et al, 1992b;Mathai and Gopinath, 1985;Wilkin and Jolley, 1979).…”
Section: Discussionmentioning
confidence: 97%
“…However, comparing outpatient and inpatient samples of schizophrenic subjects, Johnstone et al (1 98 1) concluded that the severe cognitive deficits they found were more likely due to the disease process than the circumstances of its treatment. Subsequent research has reinforced a lack of association between length of illness and cognitive deficit in schizophrenia (Harvey eta!., 1992;Mathai and Gopinath, 1985). Other research suggests that identifiable cognitive deficits may predate schizophrenia onset (Cornblatt and Erlenmeyer-Kimling, 1985) and are present even during periods of relative remission (Asarnow and MacCrimmon, 1978;Harvey et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of prolonged inpatient stay is advocated by many as potentially therapeutic and feasible with adequate community support (Bland et al ., ; Caton, ; Gorecka and Czernikiewicz, ; Malone et al ., ; Tasic et al ., ). In contrast, other investigators (Johnstone et al ., ; Mathai and Gopinath, ) suggest that long‐term hospital care itself has adverse effect on the social deficits in chronic schizophrenia and that long‐term patients show distinctive features of a protracted disease process that are not caused by hospitalization. Rossler et al ., () suggested that it is not the location of care that influences symptom patterns and social functioning, but rather the amount of social and especially family support that is provided in different settings.…”
Section: Introductionmentioning
confidence: 99%